2023
DOI: 10.3389/fimmu.2023.1184700
|View full text |Cite
|
Sign up to set email alerts
|

Six potential biomarkers in septic shock: a deep bioinformatics and prospective observational study

Abstract: BackgroundSeptic shock occurs when sepsis is related to severe hypotension and leads to a remarkable high number of deaths. The early diagnosis of septic shock is essential to reduce mortality. High-quality biomarkers can be objectively measured and evaluated as indicators to accurately predict disease diagnosis. However, single-gene prediction efficiency is inadequate; therefore, we identified a risk-score model based on gene signature to elevate predictive efficiency.MethodsThe gene expression profiles of GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…Our study revealed an upregulation of RGL4 in pediatric sepsis cases, associated with an increased risk of the condition. This nding aligns with the work of C. Kong et al , who identi ed RGL4 as a key player in the in ammatory response in adult sepsis patients 15 . However, our analysis extends this understanding to the pediatric population, suggesting that the gene's role in exacerbating sepsis may be consistent across age groups.…”
Section: Discussionsupporting
confidence: 91%
“…Our study revealed an upregulation of RGL4 in pediatric sepsis cases, associated with an increased risk of the condition. This nding aligns with the work of C. Kong et al , who identi ed RGL4 as a key player in the in ammatory response in adult sepsis patients 15 . However, our analysis extends this understanding to the pediatric population, suggesting that the gene's role in exacerbating sepsis may be consistent across age groups.…”
Section: Discussionsupporting
confidence: 91%
“…Firstly, S100A12 has been identified as a key molecule, playing a crucial role in the immune and inflammatory responses in IE patients ( 7 ), while primarily released at the infection site in sepsis patients ( 25 ). Additionally, CD177 showed significantly increased expression in sepsis patients ( 26 ), whereas IRAK3 is associated with the immune suppression stage ( 27 ). Beyond these confirmed genes, this study also discovered three potential diagnostic genes for IE (CD177, IRAK3, RNASE2) and one potential diagnostic gene for sepsis (RNASE2) for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Boruta is a feature selection method based on random forest, which randomly destroys each real feature sequentially, evaluates the importance of each feature, and iteratively deletes the features with low correlation to find the best variables. 39,40 We further performed a signature protein screen for 51 upregulated proteins by using the Boruta package. As shown in Fig.…”
Section: Profiling Urinary Ev Proteomes Of Prostate Cancer Patients T...mentioning
confidence: 99%